Tumor Resection Induces Alterations on Serum Phospholipidome of Liver Cancer Patients. Issue 2 (11th February 2020) - Martín‐Sierra, Carmen; Colombo, Simone; Martins, Ricardo; Laranjeira, Paula; Melo, Tânia; Abrantes, Ana Margarida; Oliveira, Rui Caetano; Tralhão, José Guilherme; Botelho, Maria Filomena; Furtado, Emanuel; Domingues, Pedro; Domingues, M. Rosario; et al.
Abstract: Hepatocellular carcinoma and cholangiocarcinoma are the most common primary malignant liver tumors. Since the liver plays a key role in lipid metabolism, the study of serum phospholipid (PL) profiles may provide a better understanding of alterations in hepatic lipid metabolism. In this study, we used a high‐resolution HILIC‐LC–MS lipidomic approach to establish the serum phospholipidome profile of patients with liver cancer before (T0) and after tumor resection (T1) and a control group (CT) of healthy individuals. After the analysis of PL profiles, we observed that the phospholipidome of patients with liver cancer was significantly modified after the tumor resection procedure. We observed an upregulation of some phosphatidylcholine (PtdCho) species, namely, PtdCho(36:6), PtdCho(42:6), PtdCho(38:5), PtdCho(36:5), PtdCho(38:6) and choline plasmalogens (PlsCho), and/or 1‐ O ‐alkyl‐2‐acyl‐glycerophosphocholine (PakCho) in patients with liver cancer at T0 compared to the CT group, and a downregulation after tumor resection (T1) when compared to T0. These results show that LC–MS can detect different serum PL profiles in patients with liver cancer, before and after tumor resection, by defining a specific PL fingerprint that was used to determine the effect of tumor and tumor resection on lipid metabolism.